The Possibility Investigation of Medical Electron Beam Shaping Using Devices Made from Plastics with Metallic Impurities; Physics of Atomic Nuclei; Vol. 87, iss. 12 - Bushmina E. A. Elizaveta Alekseevna; Bulavskaya A. A. Angelina Aleksandrovna; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Saburov V. G. Vyacheslav Olegovich; Stuchebrov S. G. Sergey Gennadevich (2024, 2024)
In modern practice, collimators are employed in electron beam therapy to shape the irradiation field into standard configurations. However, tumors often have complex shapes, requiring the use of collimators with individually created collimation windows typically made of metal alloys. The production of such devices is time-consuming, limiting their widespread use. A promising approach to collimator manufacturing is three-dimensional printing, using fused filament fabrication that allows the production of three-dimensional objects quickly and accurately. The polymer materials used today allow the 3D printing of products with densities up to 1.3 g/cm3, requiring the use of a relatively thick collimator. This work proposes using plastics infused with metal impurities for 3D printing collimators created for electron beam therapy. Monte Carlo numerical simulation is performed to calculate the collimator thickness required for the effective absorption of electron beams in the range of therapeutic energies. A modular collimator is therefore designed and created by 3D printing that offering the possibility of varying the diameter of the collimation window from 0.5 to 6 cm. Based on experimental data obtained for a medical electron beam with an energy of 6 MeV, it is found that the 3D printed device can effectively shape a radiation field corresponding to the chosen diameter of the collimation window. Features of using a plastic collimator to shape the field of an electron beam when planning electron beam treatment must be considered